Multiple-objective optimization of methanol/diesel dual-fuel engine at low loads: A comparison of reactivity controlled compression ignition (RCCI) and direct dual fuel stratification (DDFS) strategies. (15th February 2020) - Li, Yaopeng; Jia, Ming; Xu, Leilei; Bai, Xue-Song
Highlights: First study of methanol/diesel DDFS engine at low loads is conducted. Two-stage combustion with tri-modal heat release is identified in DDFS engine. A novel solution is developed to improve performance of LTC engine at low loads. A guideline for optimal parameters in different combustion modes is summarized. A co-optimization strategy is proposed for further improving engine performance. Abstract: Reactivity controlled compression ignition (RCCI) engines suffer from low thermal efficiency at low loads due to the high hydrocarbon and carbon monoxide emissions. Correspondingly, a direct dual fuel stratification (DDFS) combustion mode is investigated by directly injecting methanol and diesel into cylinder. Multi-objective optimization and detailed comparison are first conducted for the two engine strategies. Compared to RCCI, the optimized DDFS case shows higher thermal efficiency, lower emissions, lower demand for the in-cylinder initial temperature, and higher potential of energy recovery. Different from the single-stage combustion in RCCI, DDFS shows a two-stage combustion, the second stage of which is owing to its near-top dead center injection of methanol. Compared to RCCI, DDFS requires a lower initial temperature to retard combustion phasing, and a larger amount of exhaust gas recirculation rate to control nitrogen oxide and ringing intensity. The optimized methanol fraction and injection timings of diesel are similar for RCCI and DDFS, and they are determined in compromise of combustion efficiency and heat transfer loss. A large spray-included angle of diesel injector is preferable for RCCI to target diesel spray to the piston lip. In DDFS, a small spray-included angle of diesel injector is needed for more complete fuel oxidation, and a medium spray-included angle of methanol injector is required to avoid excessive heat transfer loss. Due to the non-sooting nature of methanol, DDFS produces as low soot emissions as RCCI. The present study shows that the co-optimization of operating parameters and fuel properties offers a promising approach to meet the more stringent regulation on efficiency and emission.